Dipole blockade and quantum information processing in mesoscopic atomic ensembles. - Lukin, MD; Fleischhauer, M; Cote, R; Duan, L; Jaksch, D; Cirac, J; Zoller, P (2001)
We describe a technique for manipulating quantum information stored in collective states of mesoscopic ensembles. Quantum processing is accomplished by optical excitation into states with strong dipole-dipole interactions. The resulting "dipole blockade" can be used to inhibit transitions into all but singly excited collective states. This can be employed for a controlled generation of collective atomic spin states as well as nonclassical photonic states and for scalable quantum logic gates. An example involving a cold Rydberg gas is analyzed.